A novel protein biochip screening serum anti-sperm antibody expression and natural pregnancy rate in a follow-up study in Chinese infertility. Issue 2 (11th February 2020) - Xu, Feihong; Ye, Lei; Hu, Yuan; Cai, Chengyun; Wang, Zhen; Fan, Liqing; Song, Lihua; Xu, Zhenshan; Du, Weidong
Abstract: Production of anti-sperm antibody (ASA) often suffers from autoimmune reaction against sperms in human infertility. The antibodies are measured in both blood and seminal plasma of males. Here, we reported a simple protein biochip methodology that takes advantage of a functionalized self-assembled monolayer modified by N-hydroxysuccinimide (NHS) and enables identification of anti-sperm antibody in Chinese male infertility. To validate this biochip platform, we immobilized purified sperm protein on the biochip surface and tested a variety of parameters in quality controls for the protein assay, respectively. Then, we analyzed serum samples from 368 patients with infertility and 116 healthy donors by means of this biochip simultaneously. We found that positive rate of serum ASA was 20.92% (77/368) in the cases and 1.72% (2/116) in the controls, respectively. Furthermore, we further corroborated the biochip assay in comparison with ELISA method. We found that both methods were compatible for the detection of serum ASA in the patients. In addition, a follow-up study for natural conception in ASA-positive and ASA-negative patients was conducted. The result showed a significant correlation between serum ASA expression and natural pregnancy rate 6.5% in ASA-positive patients while 18.9% in ASA-negative patients, indicating the potential roles of ASA in naturally reproductive processes.